Effective self-marketing model - L. A. Gladkova (Вестник университета)
The purpose of the article is to develop a theoretical model of effective self-marketing with the allocation of specific blocks, factors and results of career development. Currently, there is no system model of the self-marketing process within the framework of existing concepts, which limits the possibilities of developing scientifically based proposals for its effective technology. The formation of the model consists of three stages. Stage I – “Self-orientation”, takes into account the individual psychological characteristics of the individual, which relates to the sphere of the subject of labor and is implemented through introspection, career strategy planning and self-organisation. Stage II – “Orientation to career conditions”, takes into account the requirements of the sphere of professional activity and is implemented by analysing the conditions of the career environment and career space. Stage III – “Self-expression in the career space”, taking into account the requirements of the professional sphere and one’s own identity, involves managing an individual image, and self-presentation of the subject of labor. It is proposed to evaluate the result of self-marketing on the basis of a combination of objective and subjective criteria: the degree of achievement of the set goals of professional activity and the experience of satisfaction with its results.